Saúde emocional do estudante na Educação Básica na pandemia da Covid-19: revisão de escopo - SOARES, Rosely Machado (2023)
The emotional health of students in basic education during the COVID-19 pandemic led young people to develop serious psychological disorders. The aim of the present study was to describe and analyze the emotional health of elementary school students before and during the Covid-19 pandemic. A scope review was carried out, consulting peer-reviewed studies published in national journal between 2019 and 2022. The search was carried out in three databases (CAPES; SciELO; APA) based on the descriptors “psychological health”; student*; “basic education”, with the help of the Boolean OR. The steps proposed by the Joana Briggs Institute were followed: 1-Elaboration of the research question; 2-Identification of the studies; 3-Selection of studies; 4-Data extraction; 5-Gather, summarize and report the research results; and 6-Consult. The problem question was: How was the emotional health of elementary school students reported, before and during the Covid-19 pandemic? In total, 30.352 references were found, with two remaining for final review after screening. The results showed five psychological factors in elementary school students that would affect their emotional health: insomnia; psychological disorder; anxiety; depression and lack of emotional control. It is concluded that there are few studies in Portuguese language, and it is suggested that more research be developed on the subject.